Regulation of autophagy, lipid metabolism, and neurodegenerative pathology by heparan sulfate proteoglycans - Schultheis, Nicholas; Becker, Robert; Berhanu, Gelila; Kapral, Alexander; Roseman, Matthew; Shah, Shalini; Connell, Alyssa; Selleck, Scott (Frontiers in Genetics, 2023)
Heparan sulfate modified proteins are an abundant class of cell surface and extracellular matrix molecules. They serve important co-receptor functions in the regulation of signaling as well as membrane trafficking. Many of these activities directly affect processes associated with neurodegeneration including uptake and export of Tau protein, disposition of Amyloid Precursor Protein (APP)-derived peptides, and regulation of autophagy. In this review we focus on the impact of heparan sulfate modified proteins on autophagy, membrane trafficking, mitochondrial quality control and biogenesis, and lipid metabolism. Disruption of these processes are a hallmark of Alzheimer’s disease (AD) and there is evidence that altering heparan sulfate structure and function could counter AD-associated pathological processes. We describe a Drosophila model for examining presenilin function in lipid metabolism and show that knockdown of presenilin (Psn) produces a constellation of cellular deficits previously described in human cells, including accumulation of lipid, disruption of autophagosome to lysosome traffic and reduction in mitochondrial size and number. Inhibition of heparan sulfate biosynthesis has opposing effects on all these cellular phenotypes, increasing mitochondrial size, stimulating autophagy flux to lysosomes, and reducing the level of intracellular lipid. These findings suggest a potential mechanism for countering pathology found in AD and related disorders by altering heparan sulfate structure and influencing cellular processes disrupted broadly in neurodegenerative disease. Vertebrate and invertebrate model systems, where the cellular machinery of autophagy and lipid metabolism are conserved, continue to provide important translational guideposts for designing interventions that address the root cause of neurodegenerative pathology.